Linking activity and function to ecosystem dynamics in a coastal bacterioplankton community - Gifford, Scott M.; Sharma, Shalabh; Moran, Mary Ann (Frontiers in Microbiology, 2014)
For bacterial communities containing hundreds to thousands of distinct populations, connecting functional processes and environmental dynamics at high taxonomic resolution has remained challenging. Here we use the expression of ribosomal proteins (%RP) as a proxy for in situ activity of 200 taxa within 20 metatranscriptomic samples in a coastal ocean time series encompassing both seasonal variability and diel dynamics. %RP patterns grouped the taxa into seven activity clusters with distinct profiles in functional gene expression and correlations with environmental gradients. Clusters 1-3 had their highest potential activity in the winter and fall, and included some of the most active taxa, while Clusters 4-7 had their highest potential activity in the spring and summer. Cluster 1 taxa were characterized by gene expression for motility and complex carbohydrate degradation (dominated by Gammaproteobacteria and Bacteroidetes), and Cluster 2 taxa by transcription of genes for amino acid and aromatic compound metabolism and aerobic anoxygenic phototrophy (Roseobacter). Other activity clusters were enriched in transcripts for proteorhodopsin and methylotrophy (Cluster 4; SAR11 and methylotrophs), photosynthesis and attachment (Clusters 5 and 7; Synechococcus, picoeukaryotes, Verucomicrobia, and Planctomycetes), and sulfur oxidation (Cluster 7; Gammaproteobacteria). The seasonal patterns in activity were overlain, and sometimes obscured, by large differences in %RP over shorter day-night timescales. Seventy-eight taxa, many of them heterotrophs, had a higher %RP activity index during the day than night, indicating strong diel activity at this coastal site. Emerging from these taxonomically- and time-resolved estimates of in situ microbial activity are predictions of specific ecological groupings of microbial taxa in a dynamic coastal environment.